PLANKTON CONCENTRATION MODELING IN THE SOUTHERN WATERS OF NUSA TENGGARA DURING THE TROPICAL CYCLONE SEROJA - Avrionesti, Avrionesti (Universitas Methodist Indonesia, 2023)
Tropical Cyclone Seroja is one of the unique cyclone phenomena that occured in Indonesian waters. To determine its effect to the plankton concentration in East Nusa Tenggara Waters, 1-D Nutrient, Phytoplankton, Zooplankton, and Detritus (NPZD) ecosystem modeling was carried out. The temperature changes caused by the cyclone has a direct impact on the phytoplankton concentration and indirectly on zooplankton. The simulation shows that the peak concentration of phytoplankton due to TC Seroja occurred on 8-10 April 2021 (3.49 mmolC/m3), while for zooplankton it occurred on 20-22 April 2021 (8.55 mmolC/m3).